Interrelation of the level of working capability and the use of athletics at the classes of students - A.A. Tretyakov; L.N. Akulova; P.P. Kondratenko; V.V. Agoshkov (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the effectiveness of the use of athletics in the educational process of students to increase the level of working capacity. Methods and structure of the study. The scientific work was carried out for four months, girls and boys, studying in the 2nd year, took part in it. To organize the experiment, control (45 people) and experimental (48 people) groups were identified. The students of the control group studied according to the work program for higher educational institutions. The students of the experimental group were offered systematic classes with cross-country training and elements of athletics. Results and conclusions. The test results have a positive trend, characterizing the growth of physical and mental performance in young people. In this example, athletics were used. Obviously, the use of products from other cyclic sports will also have a positive impact on the level of performance, which gives young people a choice.